2016
DOI: 10.1007/s00134-016-4536-8
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal life support during cardiac arrest and cardiogenic shock: a systematic review and meta-analysis

Abstract: PurposeVeno-arterial extracorporeal life support (ECLS) is increasingly used in patients during cardiac arrest and cardiogenic shock, to support both cardiac and pulmonary function. We performed a systematic review and meta-analysis of cohort studies comparing mortality in patients treated with and without ECLS support in the setting of refractory cardiac arrest and cardiogenic shock complicating acute myocardial infarction.MethodsWe systematically searched MEDLINE, EMBASE, the Cochrane Central Register of Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
237
0
24

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 456 publications
(285 citation statements)
references
References 36 publications
6
237
0
24
Order By: Relevance
“…For example, VA-ECMO implantation is frequently performed in the angiography suite which in itself might be a marker of patient selection and percutaneous techniques furthermore seem to be associated with better outcomes [14]. It is essential that the cumulative evidence is systematically reviewed and presented as done by Ouweneel and colleagues [15] in a meta-analysis recently published in Intensive Care Medicine. The meta-analysis supports the results by de Chambrun et al [13] of improved survival using VA-ECMO in patients with cardiogenic shock after acute myocardial infarction as well as in refractory cardiac arrest, with improved Fig.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, VA-ECMO implantation is frequently performed in the angiography suite which in itself might be a marker of patient selection and percutaneous techniques furthermore seem to be associated with better outcomes [14]. It is essential that the cumulative evidence is systematically reviewed and presented as done by Ouweneel and colleagues [15] in a meta-analysis recently published in Intensive Care Medicine. The meta-analysis supports the results by de Chambrun et al [13] of improved survival using VA-ECMO in patients with cardiogenic shock after acute myocardial infarction as well as in refractory cardiac arrest, with improved Fig.…”
mentioning
confidence: 99%
“…The meta-analysis supports the results by de Chambrun et al [13] of improved survival using VA-ECMO in patients with cardiogenic shock after acute myocardial infarction as well as in refractory cardiac arrest, with improved Fig. 1 Trial sequential analysis (TSA) for a relative risk reduction of mortality (left-hand graph) or unfavourable neurological outcome (right-hand graph) of 30% by VA-ECMO in refractory cardiac arrest and in cardiogenic shock following acute myocardial infarction using data from all studies included by Ouweneel et al [15]. Eleven studies including 2973 patients demonstrated a 50% relative risk reduction for death.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Beobachtungsstudien deuten darauf, dass die eCPR bei diesen selektierten IHCA-und OHCAPatienten im Vergleich mit der konventionellen CPR mit einer Zunahme der Überlebensrate von bis zu 30 % einhergeht [4,[13][14][15][16][17][18][19][20][21][22]. In einer Metaanalyse zeigte sich eine um 13 % verbesserte Überlebenswahrscheinlichkeit im Vergleich zur konventionellen CPR (95 %-Konfidenzintervall [95 %-KI] 6-20 %; p < 0,001; "number needed to treat" 7,7; [23] …”
unclassified
“…So far, it is clear that this syndrome, with a stable mortality rate >40% as reported in most recent literature (1), requires a specific therapy. On top of medical therapy, mechanical circulatory support has emerged as the mainstay treatment for cardiogenic shock (1,2).…”
mentioning
confidence: 99%